Integracyjny wymiar współczesnej analizy dyskursu w świetle prac językoznawczej szkoły francuskiej - Szczepankowska, Irena (Stylistyka, 2020)
The observations described in this páper are concemed with the linguistic discourse analysis carried out by representatives of the contemporary French school, the members o f which include among others: Jean-Michel Adam, Patrick Charaudeau, Catherine Kerbrat-Orecchioni, and Dominique Maingueneau (some of them come from Swiss and Belgian French-speaking communities). The domain of their research, the most impor- tant traditions, as well as the sources of inspiration and relations between the examined field with other scientific disciplines (not only linguistics) are the principál subjects un- der discussion in this páper. The achievements o f the French school in the area o f dis course analysis prove the integrative naturę of the disciplině, which combines various fields of study o f language, style and text, that is in particular: stylistics (including rhetoric and the theory o f a literary work of art), pragmatics and text linguistics. The author demonstrates also the significance o f the relations between discourse analysis and other Sciences: philosophy, cognítive science, psychology and sociology, at the same time emphasizing that the broadly defined inlerdisciplinary studies remain (for various reasons) in the sphere of postulates. Among the many obstacles is the separation of sociál Sciences in the 20lh century.